OTU-019 Pancreatic enzyme supplementation is associated with improved survival in inoperable pancreatic cancer. (8th June 2018) - Sinha, Rohit; Manning, Sarah; Morrison, Charlotte; Greenaway, John R; Majumdar, Debasis; Craig, Darren G; Zubair, Syed; Dean, Jeremy; Mitra, Vikramjit
Abstract : Introduction: In the UK, 85% of pancreatic cancer (PC) patients are inoperable at presentation with a median survival of 6–9 months1. BSG guidelines recommend that patients with PC should receive pancreatic enzyme supplementation to maintain bodyweight and improve quality of life1. It is not known whether pancreatic enzyme supplementation prolongs survival. In this study, we examined the impact of pancreatic enzyme supplementation in inoperable pancreatic cancer. Methods: This was a single-centre retrospective study between January 2016 and June 2017. Consecutive patients deemed inoperable in the MDT were identified. Patients were subdivided in two cohorts, pancreatic enzyme supplement (PES) and Non-PES. Date of diagnosis was determined by the date of cross-sectional imaging. Use of pancreatic enzymes was determined through patient summary care records. All cases were followed up from the date of diagnosis until the date of death or censor date (31st December 2017). Primary outcomes were all-cause mortality. Results: 62 patients were included (51 had histological confirmation, 11 were radiological diagnosis). Adenocarcinoma was the commonest histological finding. Anatomical distribution of tumours was – head/uncinate (27), neck (5), body (18) and tail (12). MPD dilatation was noted in 33 patients. The mean age among the PES and Non-PES groups were comparable at 70.9 (±9.9) and 72.2 (±9.5) years respectively. 48% were female in PES group compared with 40% in non-PES group. Median follow up was 133 days (IQR 187). Unadjusted median survival days in PES group was 221 [95% CI 107.4, 334.6] compared with 61 [95% CI 35.5, 86.5] in non-PES group. Cox regression models were fitted to adjust for effects of baseline characteristics. Survival was significantly better in PES group (Log Rank p=0.004) than that seen in non-PES group (figure 1). The survival difference remained significant after adjusting for gender, age, histology of pancreatic cancer, neutrophil to lymphocyte ratio and presenting body-mass index (n=53). Lack of pancreatic enzyme supplementation was associated with significant mortality risk, adjusted hazard ratio of 2.7 [95% CI 1.38, 5.31; p=0.004]. 21 (78%) and 17 (49%) patients in PES group (n=27) and non-PES group respectively were treated with palliative chemotherapy and the rest were treated with best supportive care. Conclusions: Our study concludes that pancreatic enzyme supplementation is associated with improved survival in inoperable pancreatic cancer. Further prospective studies are required to confirm our findings.